Prevalence and Characteristics of Osteochondrosis in Lusitano Purebred Horses - Coelho Ramos, Ana Sofia (2022)
Objectives: This is the first comprehensive study in Lusitanos that aims to study the radiographic prevalence and localisation of osteochondrosis in different joints. Methods: A radiographic protocol of the metacarpo/ metatarsophalangeal, tarsocrural and femoropatellar joints was done in 302 Lusitanos, and findings were clas- sified using a 0-4 scale: 0 - normal joint contours; 1 – minimal (minimal and smooth flattening); 2 – mild (irregularly flattening); 3 - moderate (presence of a small fragment, presence of a small rounded defect) and 4 – severe (large or multiple fragments, with a large irregular defect). Scores 1 and 2 were considered to represent OC while scores 3 and 4 corresponded to OCD Results: Abnormal findings were present in 53.31% of the horses. Most were stallions (88.74%), and the mean age was 5 ± 2.48 years (range of 1 to 12 years old). The prevalence of OC (36.75%) was higher than OCD (16.56%). The most affected joint were hocks (39.73%), followed by fetlocks (26.48%) and stifles (3.3%). OC was registered in 34.43% in hocks, 14.9% in fetlocks and 2.31% in stifles. The presence of fragments (OCD) was recorded in 6.95% of the cases in the hock, 8.93% in the fetlocks and 1.65% in the stifle. Conclusions: This Lusitano horse population has presented a high prevalence of osteochondral lesions, with a low prevalence of OCD. This study is important to ensure a rational use of Lusitano and a prospective study is required to determine the genetic variability regarding OC/OCD in this breed.